(untitled) (Research, Society and Development, 2025)
Introduction: The newborn’s skull is composed of mobile structures, allowing it to be molded and facilitating passage through the birth canal. However, during the intrauterine period and the birth process, this mobility can result in cranial deformities, such as plagiocephaly. One mechanical dysfunction that can be observed in children with cranial alterations is the presence of breastfeeding difficulties. Objective: To investigate the possible relationship between plagiocephaly and the quality of breastfeeding in newborns at the maternal-infant unit of the University Hospital of Western Paraná. Materials and Methods: The study included 79 healthy newborns between 24 and 48 hours old, where data were collected from interviews with the caregiver and from the newborn’s vaccination card, along with the performance of craniometry and assessment of breastfeeding using the LATCH tool. Results: There were no statistically significant differences in LATCH scores between normal newborns and those with plagiocephaly in the first 24 to 48 hours of life for this specific group.